THE PERBANDINGAN INTERVENSI ULTRASOUND DAN MUSCLE ENERGY TECHNIQUE DENGAN INTERVENSI ULTRASOUND DAN MCKENZIE EXERCISE TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL PADA NON-SPECIFIC LOW BACK PAIN - Wibawa, Ari; Tianing, Ni Wayan; Kinandana, Gede Parta; Juniantari, Ni Komang Ayu (Majalah Ilmiah Fisioterapi Indonesia, 2018)
This study aims to compare ultrasound and muscle energy technique interventions more effectively than ultrasound and mckenzie exercise in enhancing functional capabilities in non-specific low back pain cases. The test used is the modified oswestry low back pain disability questionnaire for measuring functional pain. Using experimental design with pre-test and post-test group design involving a sample of 32 people divided into 2 groups. Group 1 with ultrasound treatment and muscle energy technique and group 2 with ultrasound and mckenzie exercise treatment. Hypothesis test results using independent sample t-test obtained p = 0.000 with average difference in Group I 22.85 (SD 4.348) while Group II got difference average 12,86 (SD 2,797). These results show that there is a significant difference in non-specific LBP functional pain reduction between the muscle energy technique treatment group and the mckenzie exercise treatment group. Keywords: low back pain non-spesifik, modified oswestry low back pain disability questionnaire, ultrasound, muscle energy technique, mckenzie exercise